E-Access to the City? Mapping Applications for People with Disabilities - Pankau, Joanna (ETHICS IN PROGRESS, 2019)
The article focuses on the socio-spatial accessibility of the city, taking into account the phenomenon of a digitally expanding urban environment: new-media mobility conditions, intermedia dataflow, hybrid space. Therefore, turning to the problem of access and to urban mobile applications complements the problem of access to the city itself. Particular attention is focused on mapping applications, considering mapping as an expression of active city exploration “from the inside” and the process of cooperative spatial knowledge production, characterized by a critical approach. Urban mapping applications dedicated to people with disabilities can be not only a form of support when they move around the city, but also a kind of tool for co-shaping urban space – exposing inequalities and seeking ways to deconstruct socio-spatial “normalization”. In this perspective, people with disabilities, taking advantage of the new spaces of mobile accessibility, place themselves in the role of political subjects, co-creators of space, “mapping citizens” fighting for their rights as urban citizens.